Peran Media Sosial Tiktok Dalam Mempengaruhi Perilaku Sosial Remaja Di Era Digital - Octaviana, Rizka; Fidiyansyah, Amir; Asriani, Wulan (Komunika : Jurnal Ilmiah Komunikasi, 2023)
This study aims to analyze the role of the social media platform TikTok in influencing the social behavior of teenagers in the digital era. TikTok, as one of the most popular social media platforms among teenagers, offers a variety of content that is easily and quickly accessible. This research uses a qualitative approach with a case study method, involving in-depth interviews and participatory observations to collect data from a number of teenage TikTok users. The results show that TikTok has a significant impact on teenagers' social behavior, both positively and negatively. Positively, TikTok can enhance teenagers' creativity and communication skills through various challenges and educational content. On the other hand, TikTok also has the potential to cause negative behaviors such as social media addiction, social pressure to follow trends, and exposure to inappropriate content. This study concludes that it is important for parents and educators to understand the dynamics of TikTok usage by teenagers and provide appropriate guidance to minimize its negative impacts. Additionally, the active role of platform managers in monitoring content is also crucial in creating a healthy social media environment for teenagers.